TEACHING READING NARRATIVE TEXT BY IMPLEMENTING SURVEY, QUESTION, READ, RECITE, AND REVIEW (SQ3R) TECHNIQUE TO THE TENTH GRADERS OF SMAN 1 KREMBUNG - MEGA WATI, ARI (RETAIN : Journal of Research in English Language Teaching, 2015)
Abstrak Membaca merupakan bagian dari komunikasi yang terdiri dari aktivitas komunikasi dan menjadi pusat untuk menstimulasi berpikir pemahaman (Rayner, 1998). Untuk memahami sebuah teks, guru harus mengetahui suatu teknik dalam pengajaran membaca agar siswa dapat menangkap ide utama dan menjawab pertanyaan dari teks. Oleh karena itu, hal ini penting bagi seorang guru Bahasa Inggris untuk menciptakan cara yang sesuai selama proses pembelajaran. Guru harus menemukan suatu teknik yang sesuai dan menarik dalam pengajaran membaca, khususnya memahami teks yang bertujuan untuk mencapai tujuan pembelajaran. Dalam penelitian ini, survey, question, read, recite, and review (SQ3R) adalah teknik yang dapat membantu siswa menjadi lebih aktif selama proses pembelajaran. Penelitian ini bertujuan untuk menginvestigasi penerapan teknik survey, question, read, recite, and review (SQ3R) dalam pengajaran membaca teks naratif kepada siswa kelas X dari SMAN 1 Krembung. Penelitian ini merupakan penelitian descriptive qualitative. Subyek dari penelitian ini adalah siswa kelas X dari SMAN 1 Krembung di kelas X-MIA-1 pada semester dua. Data dari penelitian ini adalah hasil observasi, tugas membaca siswa, dan interview. Observasi dilakukan sebanyak tiga kali. Tugas membaca siswa diberikan setiap pertemuan. Kemudian, interview diberikan pada akhir penelitian. Data- data dianalisa secara deskriptif untuk menjawab ketiga pertanyaan penelitian. Ini menunjukkan teknik survey, question, read, recite, and review (SQ3R) dapat mendorong siswa menjadi lebih aktif dalam proses pembelajaran. SQ3R terdiri dari 5 langkah. Frank et al (2006) mengatakan bahwa kelima langkah tersebut adalah survey, question, read, recite, and review. Guru memulai dengan langkah pertama, surveying, meminta siswa untuk meninjau chapter title, headings, subheadings, words, phrases, special type, pictures, diagrams, illustrations, charts, and graphs. Langkah kedua adalah questioning. Di langkah ini, guru meminta siswa untuk memperhatikan pokok utama dari materi membaca agar mereka dapat menciptakan pertanyaan sendiri dari judul dan gambar. Langkah ketiga adalah reading. Di langkah ini, guru meminta siswa membaca teks secara perlahan yang bertujuan untuk mencari ide dan informasi yang dibutuhkan untuk menjawab pertanyaan. Langkah keempat adalah reciting. Di langkah ini, guru meminta siswa untuk menjawab pertanyaan yang telah mereka buat untuk mengingat informasi yang telah mereka pelajari dari teks. Kemudian, langkah terakhir adalah reviewing. Di langkah ini, guru meminta siswa untuk melihat ulang dan merefleksi materi bacaan dengan cara melengkapi ide- ide yang tercantum di teks. Mereka juga merangkum dengan cara mengambil informasi penting dan mengabaikan informasi yang kurang penting. Guru dapat menerapkan teknik survey, question, read, recite, and review (SQ3R)menurut teori yang disarankan oleh Frank et al (2006). Hasil dari penelitian menunjukkan bahwa guru telah menerapkan teknik survey, question, read, recite, and review (SQ3R) dalam pengajaran membaca teks naratif dengan baik. Dalam kesempatan ini, guru sudah cukup baik ketika memimpin dan memfasilitasi siswa untuk menerapkan teknik survey, question, read, recite, and review (SQ3R) dalam pengajaran membaca teks naratif. Sementara itu, hasil dari tugas membaca yang diberikan kepada siswa menunjukkan bahwa mereka berada pada tiga tingkatan membaca dengan penerapan teknik survey, question, read, recite, and review (SQ3R). Tingkatan tersebut adalah acceptable, good, dan best. Ditambah lagi,hasil interview yang diberikan kepada siswa menunjukkan bahwa kebanyakan siswa antusias dalam mengikuti proses belajar mengajar dengan menerapkan survey, question, read, recite, and review (SQ3R) yang dilakukan oleh guru. Disudut pandang mereka, pengajaran membaca dengan menerapkan teknik survey, question, read, recite, and review (SQ3R) dapat membuat mereka menjadi lebih aktif karena guru mendorong mereka untuk belajar secara mandiri dengan menciptakan beberapa pertanyaan sendiri. Disamping itu, teknik ini dapat membuat proses belajar mengajar lebih menarik. Kesimpulannya, survey, question, read, recite, and review (SQ3R) adalah teknik yang baik untuk mengajar membaca teks naratif, khususnya pengajaran membaca teks naratif kepada siswa kelas X dari SMAN 1 Krembung. Kata kunci: Membaca, TeksNaratif, Teknik SQ3R. Abstract Reading is a kind of communication which consists of communicative activity and become the center to stimulate thinking for comprehension (Rayner, 1998). To comprehend a text, teachers have to know a technique in teaching reading so the students can catch up the main idea and answer the following questions from the text. Therefore, it is important for an English teacher to create a proper way during teaching and learning process. The teacher should be able to find an appropriate and interesting technique in teaching reading, particularly comprehending the text in order to reach the goal of learning. In this study, survey, question, read, recite, and review (SQ3R) is a technique that helps the students become more active in teaching and learning process. This research aims to investigate the implementation of survey, question, read, recite, and review (SQ3R) technique in teaching reading narrative text to the tenth graders of SMAN 1 Krembung. This research is descriptive qualitative research. The subject of this research is the tenth graders of SMAN 1 Krembung at class X-MIA-1 on the second semester. The data in this research are the result of observation, students’ reading task and interview. The observations were conducted three times. The students’ reading task were given in every meetings. Then, the interview was given at the end of the observation. The data were analyzed descriptively to answer those three research questions. It clearly showed that survey, question, read, recite, and review (SQ3R) technique can encourage the students become more active in the teaching and learning process. SQ3R has five steps. Frank et al (2006) state that those five steps are survey, question, read, recite and review. The teacher starts with the first step, surveying, by asking the students to check out chapter title, headings, subheadings, words, phrases, special type, pictures, diagrams, illustrations, charts, and graphs. The second step is questioning. In this step, the teacher asks the students to focus on the main points of reading material so they can create questions from the title and picture for themselves. The third step is reading. In this step, the teacher asks the students to read the reading passage carefully to search of ideas and information in order to help answer the questions raised. The fourth step is reciting. In this step, the teacher asks the students to answer their questions that they have made in order to remember the information that they have learned from the text. Then, the last step is reviewing. In this step, the teacher asks the students to review and reflect on material by organizing and elaborating on ideas encountered in text. They also summarize by taking the important information and ignoring the unimportant information. The teacher could implement survey, question, read, recite, and review (SQ3R) technique properly according to framework suggested by Frank et al (2006). The result of observations also show that the teacher had already implemented survey, question, read, recite, and review (SQ3R) technique in teaching reading narrative text well. In this case, the teacher was quite good when guiding and facilitating the students to implement survey, question, read, recite, and review (SQ3R) technique in teaching reading narrative text. Meanwhile, the result of students’ reading task given to the students shows that they were in three levels of reading by implementing survey, question, read, recite, and review (SQ3R) technique. Those levels are acceptable, good and best level. In addition, the result of interview given to the students shows that most of the students were enthusiastic followed the teaching and learning process implementing survey, question, read, recite, and review (SQ3R) technique conducted by the teacher. In their point of view, teaching reading by implementing survey, question, read, recite, and review (SQ3R) technique can make them to be more active because the teacher encouraged them to learn independently by creating some questions by themselves. Besides, it can make the teaching and learning process more interesting. In conclusion, survey, question, read, recite, and review (SQ3R) is a good technique to teach reading narrative text, especially teaching reading narrative text to the tenth graders of SMAN 1 Krembung. Key words: Reading, Narrative Text, SQ3R Technique.